Caracterização microestrutural e mecânica da liga AA2024 conformada por spray e processada termomecanicamente - Asato, Gabriel Hitoshi (2019)
This work aimed to evaluate the possibility of combining spray forming processing with mechanical processing techniques (for instance, extrusion, rotary forging, and equal-channel angular pressing (ECAP)) to be used as processing routes for reuse of aluminum alloys. In the specific case of the AA2024 alloy, in applications nobler than the intended for production of casting alloys. For such an aiming, the final alloy must have a refined microstructure, solubilized alloying elements, be entirely homogeneous, absent of porosity that can affect mechanical properties, and chemical composition similar to the as received alloy. Our results have shown that, after spray forming, the microstructure presented equiaxed grains with an average size of 50 μm, alloying elements more solubilized than the as received alloy and a significant fraction of porosity. Chemical analysis of the deposit showed chemical composition with a small variation in composition, but still inside the allowed values imposed by the ASTM standard. The deposit was machined into cylindrical samples to be processed by extrusion and rotary forging and square-like samples to be processed by ECAP. The combination of rotary forging and ECAP were also performed. After processing, microstructural characterizations were accomplished to verify porosity closing and microstructure refinement. Mechanical compression tests were conducted to evaluate the mechanical strength of the processed alloys compared to the as received one. Results obtained from mechanical tests for the alloys processed by extrusion and rotary forging presented higher values than for the initial alloy. However, ECAP presented a decrease in mechanical resistance. Concerning the microstructure, the grains remained elongated, characteristic of mechanically processed alloys without recrystallization, secondary phases were sufficiently solubilized, no coring effect was observed in grains, and the porosity was significantly reduced.